SINTESIS DAN UJI ANTIBAKTERI SENYAWA (E)-1-(2-KLOROFENIL)-3-PTOLILPROP- 2-EN-1-ON - Brahmana, Eti Meirina (Edu Research, 2015)
Halogen substituted analogoues compounds chalcone, (E)-1-(2-chlorophenyl)-3-p-tolylprop-2-en-1-on, were synthesized from 4-isopropyl benzaldehyde as aldehydes with 2-chloroacetophenone as ketones by using aldol condensation reaction. The compound resulted rendement with value of 60,08% and characterized by using UV, IR, MS, and 1HNMR. Test of antibacterial activity using agar diffusion method showed that the compound (E)-1-(2-chlorophenyl)-3-p-tolylprop-2-en-1-on potentialas an antibacterial